IMPLEMENTASI MODEL MIND MAPPING DALAM PEMBELAJARAN SEJARAH PADA PESERTA DIDIK KELAS X SMAN 3 PONTIANAK : Pembelajaran Sejarah, Model Mind Mapping - Dewi, Purnama; Firmansyah, Andang; Firmansyah, Haris (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
CT This research was conducted to investigate how the mind mapping model isapplied in history learning for tenth-grade students at SMAN 3 Pontianak. The type ofresearch used in this study is qualitative descriptive research. The informants in this study arehistory teachers, tenth-grade students, and the curriculum representative. Data collectiontechniques using observation, interviews, and documentation. Data analysis techniquesconsist of data collection, data reduction, data presentation, and conclusion drawing. Theresults of this study indicate that: First, the planning of history lessons conducted by theteacher includes the preparation of teaching materials in the form of teaching modules,teaching materials, and lesson content. Secondly, the implementation of history learningconsists of introductory, core, and closing activities. Learning activities using the mindmapping model have not been optimal, as they do not align with the teaching modulespreviously prepared by the teacher. Thirdly, the assessment of history learning in terms ofknowledge and skills is conducted through assigned tasks, while the attitude aspect isevaluated through attendance.